How do users of a ‘digital-only’ contraceptive service provide biometric measurements and what does this teach us about safe and effective online care? A qualitative interview study - Paula Baraitser; Caroline Free; Hannah Mcculloch; Alessandra Morelli (BMJ Open, 2020)
Objectives To describe user experience of obtaining and uploading biometric measurements to a ‘digital-only’ contraceptive service prior to a prescription for the combined oral contraceptive (COC). To analyse this experience to inform the design of safe and acceptable ‘digital-only’ online contraceptive services.Setting An online contraceptive service available free of charge to women in South East London, UK.Participants Twenty participants who had ordered the combined oral contraceptive (COC) online. Our purposive sampling strategy ensured that we included participants from a wide range of ages and those who were and were not prescribed the COC.Intervention A ‘digital-only’ contraceptive service that prescribes the COCafter an online medical history and self-reported height, weight and blood pressure (BP) with pills prescribed by a GMC registered doctor, dispensed by an online pharmacy and posted to the user.Design Semistructured interviews with a purposive sample of 20 participants who were already enrolled in a larger study of this service.Analysis Inductive, thematic analysis of the interviews assisted by NVivo qualitative analysis software.Results Users valued the convenience of ‘digital-only care’ but experienced measuring BP but not height or weight as a significant barrier to service use. They actively engaged in work to understand and measure BP through a combination of recent/past measurements, borrowed machines, health service visits and online research. They negotiated tensions around maintaining a trusting relationship with the service, meeting its demands for accurate information while also obtaining the contraception that they needed.Conclusion Digital strategies to build trusting clinical relationships despite a lack of face-to-face contact are needed in ‘digital-only’ health services. This includes acknowledgement of work required, evidence of credible human support and a digital interface that communicates the health benefits of collaborating with an engaged clinical team.